SURVEI MINAT MAHASISWA BARU TAHUN 2020 STMIK AGAMUA WAMENA TERHADAP KOMPUTER - I Gusti Ayu Ngurah Kade Sukiastini; Marthen Medlama (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine the interest of new students in STMIK Agamua Wamena of 2020 towards computers. This is a descriptive research with survey method. The type of data collection from this research is distributing questionnaires using a list of questions that have been prepared previously and used as a guide in digging up data. The questionnaire instrument consists of 10 (ten) statements. The questionnaire was tested for validity and reliability using SPSS. The questionnaire was prepared using a Likert scale of 1-4 (4 = strongly agree; 3 = agree; 2 = disagree; 1 = strongly disagree). The analytical method used is simple statistical analysis, by accumulating the number of points for each parameter that is visualized into a graph. The results of this study are the interest or interest of new students towards computers is quite large, as seen from the number of percentages who agree and strongly agree more than those who strongly disagree and disagree. Keywords: Interest, New Student, Computer